Learning from Megadisasters: Lessons from the Great East Japan Earthquake - Ranghieri, Federica (World Bank, 2015)
The successes of Japan?s disaster risk management (DRM) system as well as the ways in which that system could be improved are reflected in the lessons drawn from the Great East Japan Earthquake (GEJE) and presented in the initial reports from the Learning from Megadisasters project. The GEJE was the first disaster ever recorded that included an earthquake, a tsunami, a nuclear power plant accident, a power supply failure, and a large-scale disruption of supply chains. Extreme disasters underscore the need for a holistic approach to DRM. Single-sector development planning cannot address the complexity of problems posed by natural hazards, let alone megadisasters, nor can such planning build resilience to threats. Faced with complex risks, Japan chose to build resilience by investing in preventative structural and nonstructural measures; nurturing a strong culture of knowledge and learning from past disasters; engaging in wise DRM regulation, legislation, and enforcement; and promoting cooperation among multiple stakeholders, between government agencies and ministries, between the private sector and the government, and among multiple levels of governance, from local to national to international. The book consolidates a set of 36 Knowledge Notes, research results of a joint study undertaken by the Government of Japan and the World Bank. These notes highlight key lessons learned in seven DRM thematic clusters?structural measures; nonstructural measures; emergency response; reconstruction planning; hazard and risk information and decision making; the economics of disaster risk, risk management, and risk financing; and recovery and relocation. Aimed at sharing Japanese cutting-edge knowledge with practitioners and decision makers, this book provides valuable guidance to other disaster-prone countries for mainstreaming DRM in their development policies and weathering their own natural disasters.